AB0257 ASSESSMENT OF PHYSICAL DYSFUNCTION IN PATIENTS WITH RHEUMATOID ARTHRITIS WHO PLANNED PREGNANCY FROM THE IORRA COHORT. (13th June 2020) - Ochiai, M.; Tanaka, E.; Inoue, E.; Abe, M.; Sugano, E.; Sugitani, N.; Saka, K.; Yoko, H.; Yamaguchi, R.; Sugimoto, N.; Katsunori, I.; Nakajima, A.; et al.
Abstract : Background: It has been reported that female rheumatoid arthritis (RA) patients have a longer time to pregnancy than healthy women (1), and that high Disease Activity Score with 28 joint count (DAS28) -CRP in preconception increases the frequency of infertility (2). Before the era of biologics, RA treatment tended to be inadequate from pregnancy planning to the end of lactation. And it was not uncommon for female RA patients to be unable to get pregnant or develop physical dysfunction as a result of insufficient control of the disease. There are some reports of disease activity during pregnancy and postpartum in RA patients, and the effects of RA disease activity on pregnancy and childbirth outcomes (3-5), but there are few reports focusing on the physical function during pregnancy planning of RA patients. Objectives: To investigate disease activity and physical function in female patients with RA who planned and didn't plan pregnancy. Methods: The IORRA cohort is a large, single institute-based, observational cohort of RA patients established at the Institute of Rheumatology, Tokyo Women's Medical University, in 2000. We identified female RA patients aged 20-49 years who answered 'pregnant' or 'delivered' in the IORRA survey in 2010-2015 and whose pregnancy and the pregnancy planning time was confirmed in the medical records, and defined them as the pregnancy planning (PP) group. Matched control was extracted at 1:3 ratio from patients without pregnancy plan based on entry time, age, RA disease duration, DAS28-CRP, Japanese version of Health Assessment Questionnaire (J-HAQ) score, and comorbidities. The primary endpoint was J-HAQ at 3years from the baseline, which was defined as the most recent IORRA survey before planning pregnancy. The mixed-effect model for repeated measures was used to analyze group difference. Results: There were 40 patients in the PP group (average 32.2 years, disease duration 5.7 years, DAS28-CRP 1.7, J-HAQ 0.26), and 120 patients in the control group (average 32.4 years, disease duration 5.9 years, DAS28-CRP 1.7, J-HAQ 0.21). The proportion of user and dosage of MTX and glucocorticoid (GC) and bDMARDs user at baseline were comparable between the groups (MTX: PP 87.5% [9.8 mg/week], control 85.0% [8.8 mg/week]; GC: PP 32.5% [3.6 mg/day], control 27.5% [4.4 mg/day]; bDMARDs: PP 40.0%, control 27.5%). DAS28-CRP at year 3 of the PP group elevated and was higher than the control group (PP 2.3, control 1.7, p<0.01), while J-HAQ was stable over the observation period and did not differ significantly at year 3 (PP 0.21, control 0.22, p=0.92). At year 3, the proportion of patients taking MTX was lower and taking GC was higher in the PP group than those in the control group (MTX: PP 36.7%, control 76.7%, p<0.01; GC: PP 70.0%, control 25.6%, p<0.01). The proportion of patients taking bDMARDs was not different in both groups (PP 36.7%, control 32.6%, p=0.68). Conclusion: Physical function in pregnancy planning patients with RA did not deteriorate as well as the control patients in clinical settings. References: [1]Arthritis Rheum. 2011;63:1517-1521. [2]Ann Rheum Dis. 2015;10:1836-1841. [3]J Rheumatol. 2015;42:1376-1382. [4]J Rheumatol. 2019;46:245-250. [5]Arthritis Care Res. 2017;69:1297-1303. Disclosure of Interests: Moeko Ochiai: None declared, Eiichi Tanaka Consultant of: ET has received lecture fees or consulting fees from Abbvie, Asahi Kasei pharma co., Bristol Myers Squibb, Chugai Pharmaceutical, Daiichi Sankyo Co., Eisai Pharmaceutical, Janssen Pharmaceutical K.K., Nippon Kayaku, Pfizer, Takeda Pharmaceutical, Taisho Toyama Pharmaceutical Co., and UCB Pharma., Speakers bureau: ET has received lecture fees or consulting fees from Abbvie, Asahi Kasei pharma co., Bristol Myers Squibb, Chugai Pharmaceutical, Daiichi Sankyo Co., Eisai Pharmaceutical, Janssen Pharmaceutical K.K., Nippon Kayaku, Pfizer, Takeda Pharmaceutical, Taisho Toyama Pharmaceutical Co., and UCB Pharma., Eisuke Inoue Speakers bureau: EI has received speaker fee from Bristol-Meyers, Pfizer, Merck serono., Mai Abe: None declared, Eri Sugano: None declared, Naohiro Sugitani: None declared, Kumiko Saka: None declared, higuchi yoko: None declared, Rei Yamaguchi: None declared, Naoki Sugimoto: None declared, Ikari Katsunori Speakers bureau: KI has received speaker's fee from Asahi Kasei Pharma Corp., Astellas Pharma Inc., AbbVie Japan GK, Ayumi Pharmaceutical Co., Bristol Myers Squibb Co., Ltd., Chugai Pharmaceutical Co., Ltd., Eis, ai Co., Ltd., Eli Lilly Japan K.K., Janssen Pharmaceutical K.K., Kaken Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Corp.Pfizer Japan Inc., Takeda Pharmaceutical Co. Ltd., Teijin Pharma Ltd and UCB Japan Co. Ltd., Ayako Nakajima Grant/research support from: AN has received research grants from Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Consultant of: AN has consultant fee from Nippon Kayaku Co. Ltd., Speakers bureau: AN has received speaker's fee from AbbVie Japan GK, Actelion Pharmaceuticals Japan LTD., Asahi Kasei Pharma Co., Astellas Pharma Inc., Ayumi Pharmaceutical Co., Bristol Myers Squibb Co., Ltd., Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Eli Lilly Japan K.K., GlaxoSmithKline K.K., Hisamitsu Pharmaceutical Co. Inc., Kyorin Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Co., Otsuka Pharmaceutical Co. Ltd., Pfizer Japan Inc., and Teijin Pharma Ltd., Atsuo Taniguchi: None declared, Hisashi Yamanaka Grant/research support from: HY has received research grant or speaker fee from AbbVie, Astellas, Ayumi, Behringer, Bristol-Meyers, Chugai, Daiichi-Sankyo, Eisai, Kaken, Nippon-Shinyaku, Novartis, Ono, Pfizer, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Teijin Pharma, Torii, UCB, YLbio., Speakers bureau: HY has received research grant or speaker fee from AbbVie, Astellas, Ayumi, Behringer, Bristol-Meyers, Chugai, Daiichi-Sankyo, Eisai, Kaken, Nippon-Shinyaku, Novartis, Ono, Pfizer, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Teijin Pharma, Torii, UCB, YLbio., masayoshi harigai Grant/research support from: AbbVie Japan GK, Ayumi Pharmaceutical Co., Bristol Myers Squibb Co., Ltd., Eisai Co., Ltd., Mitsubishi Tanabe Pharma Co., Nippon Kayaku Co., Ltd., and Teijin Pharma Ltd. MH has received speaker's fee from AbbVie Japan GK, Ayumi Pharmaceutical Co., Boehringer Ingelheim Japan, Inc., Bristol Myers Squibb Co., Ltd., Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Eli Lilly Japan K.K., GlaxoSmithKline K.K., Kissei Pharmaceutical Co., Ltd., Oxford Immuotec, Pfizer Japan Inc., and Teijin Pharma Ltd. MH is a consultant for AbbVie, Boehringer-ingelheim, Kissei Pharmaceutical Co., Ltd. and Teijin Pharma.